2014
DOI: 10.1007/s11596-014-1228-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wnt/β-catenin signaling pathway in the mechanism of calcification of aortic valve

Abstract: Aortic valve calcification is a common disease in the elderly, but its cellular and molecular mechanisms are not clear. In order to verify the hypothesis that Wnt/β-catenin signaling pathway is involved in the process of calcification of aortic valve, porcine aortic valve interstitial cells (VICs) were isolated, cultured and stimulated with oxidized low density lipoprotein (ox-LDL) for 48 h to induce the differentiation of VICs into osteoblast-like cells. The key proteins and genes of Wnt/β-catenin signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Normally, NOTCH1 signaling prevents calcification through suppression of master osteoblast transcription factor runt-related transcription factor 2 (RUNX2) whereas loss-of-function mutations in NOTCH1 result in upregulation of BMP2 [55][56][57][58][59]. In addition, activation of glycogen synthase kinase-3 (GSK-3β) and β-catenin in the Wnt/β-catenin signaling pathway also results in osteogenic differentiation of VICs via increased production of ALP [60,61]. Interestingly, methylation of NOTCH1 at the promotor side decreases NOTCH1 expression while the Wnt/β-catenin is being activated leading to transcription of the osteogenic genes RUNX2, SOX9, and BMP2 suggesting an interplay between the NOTCH1 and Wnt/β-catenin pathway [62].…”
Section: The Notch and Wnt-mediated Calcific Regulatory Pathwaysmentioning
confidence: 99%
“…Normally, NOTCH1 signaling prevents calcification through suppression of master osteoblast transcription factor runt-related transcription factor 2 (RUNX2) whereas loss-of-function mutations in NOTCH1 result in upregulation of BMP2 [55][56][57][58][59]. In addition, activation of glycogen synthase kinase-3 (GSK-3β) and β-catenin in the Wnt/β-catenin signaling pathway also results in osteogenic differentiation of VICs via increased production of ALP [60,61]. Interestingly, methylation of NOTCH1 at the promotor side decreases NOTCH1 expression while the Wnt/β-catenin is being activated leading to transcription of the osteogenic genes RUNX2, SOX9, and BMP2 suggesting an interplay between the NOTCH1 and Wnt/β-catenin pathway [62].…”
Section: The Notch and Wnt-mediated Calcific Regulatory Pathwaysmentioning
confidence: 99%
“…In addition, high serum levels of the Wnt antagonists secreted frizzled related protein-3 (sFRP-3), dickkopf-1 (DKK-1), and Wnt inhibitory factor-1 (WIF-1) were identified in patients with symptomatic aortic stenosis in contrast to healthy controls, and the circulating levels of WIF-1 and DKK-1 were found to be predictive of mortality [33]. The differentiation of porcine valve interstitial cells into osteoblast-like cells, a process involved in the calcification of the aortic valve, was found to significantly increase the expression of GSK-3β and β-catenin [34]. …”
Section: Wnt Signaling In Cardiac Repair and Diseasementioning
confidence: 99%
“…The Wnt/β-catenin pathway, in particular, is considered relevant for osteoblastic differentiation for CAVD at the molecular level [1316], as western blotting and RT-PCR analyses have confirmed the upregulation of β-catenin in calcified aortic valves and in bone in the stenotic aortic valve [17]. Oxidized low density lipoprotein leads to AV calcification in vitro and in vivo and LRP5/Wnt signal and β-catenin are related with cardiovascular calcification [14, 15, 1719]. The myofibroblastic differentiation processes of VICs have also been related to the Wnt/β-catenin signalling that depends on matrix stiffness and TGF-β1 [20].…”
Section: Introductionmentioning
confidence: 99%
“…The myofibroblastic differentiation processes of VICs have also been related to the Wnt/β-catenin signalling that depends on matrix stiffness and TGF-β1 [20]. Stimulation of porcine VICs by oxidised low density lipoprotein also induces β-catenin expression, leading to the conclusion that Wnt/β-catenin signalling plays a key role in osteoblastic VIC differentiation, thereby contributing to CAVD [14]. Similar results were published by Gao et al, who demonstrated an involvement of the Wnt/β-catenin signalling pathway in osteoblastic VIC differentiation monitored by western blotting and/or RT-PCR detection of extracellular matrix proteins and respective gene markers [21].…”
Section: Introductionmentioning
confidence: 99%